Voices From the Deep: What the Pacific Charmer Tragedy Means for Preventing Fishing Accidents - Roger Boshier (Adult Education Research Conference, 2000)
The CFV Pacific Charmer capsized, sank and two men died. Using interviews with survivors, associates of the deceased and rescuers, the author theorizes the incident and charts what needs to be done to prevent fishboat "accidents."